Use of diffusive gradients in thin films (DGT) as an early detection tool of low‐intensity leakage from CO2 storage. Issue 2 (6th November 2013) - Agnelli, Marco; Grandia, Fidel; Credoz, Anthony; Gasparini, Andrea; Bruno, Jordi
Abstract Diffusive gradients in thin films (DGT) have been tested in CO2‐rich, metal‐bearing fluids from springs in the Campo de Calatrava region in Central Spain, to assess their applicability as a monitoring tool in onshore CO2 storage projects. These films are capable of adsorbing metals and recording changes in their concentration in water, sediments, and soils. Considering that CO2 dissolution promotes metal solubilization and transport, the use of these films could be valuable as a monitoring tool of early leakage. A number of DGT have been deployed in selected springs with constant metal concentration. The studied waters show high concentrations of Fe, as high as 1 × 104 μg·L−1, Ni, Co, Zn, Cu, and Mn. Comparing re‐calculated metal concentration in DGT with metal water concentration, two different metal behaviors are observed: (i) metals with sorption consistent with the metal concentration (i.e. plotting close to the 1:1 line in a [Me]DGT: [Me]water plot), and (ii) metals with non−linear sorption, with some data showing metal enrichment in DGT compared with the concentration in water. Metals in the first group include Fe, Mn, Co, Ni, and U, and metals in the second group are Zn, Pb, Cr, Cu, and Al. From this research, it is concluded that the metals in the first group can be used to monitor potential leakage by using DGT, providing effective leakage detection even considering low variations of concentrations, episodic metal release, and reducing costs compared with conventional, periodic water sampling.